Extensive deep vein thrombosis as a complication of testicular cancer treated with the BEP protocol (bleomycin, etoposide and cisplatin): case report - Mano, Max Senna; Guimarães, José Luiz Miranda; Sutmöller, Christian Sandor Svend Chicata; Sutmöller, Sören Franz Marian Chicata; Leo, Angelo Di (São Paulo Medical Journal, 2006)
CONTEXT: There are no reports in the literature of massive deep venous thrombosis (DVT) asso- ciated with cisplatin, bleomycin and etoposide (BEP) cancer treatment. CASE REPORT: The patient was a 18 year old adolescent with a nonseminomatous germ cell tumor of the right testicle, with the presence of pulmonary, liver, and massive retroperitoneal metastases. Following radical orchiectomy, the patient started chemotherapy according to the BEP protocol (without routine prophylaxis for DVT). On day 4 of the first cycle, massive DVT was diagnosed, extending from both popliteal veins up to the thoracic segment of the inferior vena cava. Thrombolytic therapy with streptokinase was immediately started. On day 2 of thrombolytic therapy, the patient developed acute renal failure, due to extension of the thrombosis to the renal veins. Streptokinase was continued for six days and the outcome was remarkably favorable.